(untitled) (UNED Research Journal, 2021)
Introduction: Commercial egg production requires an understanding of how egg quality is affected by production conditions, housing systems, animal welfare, bird age, and breed. Objective: To describe egg characteristics of four chicken breeds in Costa Rica. Methods: We studied the egg production of four breeds, in 2017 in Turrialba, Costa Rica, recording production conditions, yield, and egg morphology and microbiology (Salmonella spp., Escherichia coli, total coliforms and total aerobic count). Results: Breeds differed in yield, and egg weight and shell thickness increased with age. Only the cage system and free-range hens had acceptable levels of microbiological contamination. Conclusions: There were differences between all the productive and morphological characteristics evaluated for the egg, when housing, age and genetics were considered.